Effectiveness and safety of a time to isolation strategy of cryoballoon ablation of atrial fibrillation: A systematic review and meta‐analysis. (8th October 2022) - Tsiachris, Dimitris; Doundoulakis, Ioannis; Antoniou, Christos‐Konstantinos; Pagkalidou, Eirini; Zafeiropoulos, Stefanos; Kordalis, Athanasios; Gatzoulis, Konstantinos A.; Chierchia, Gian‐Battista; de Asmundis, Carlo; Tsioufis, Konstantinos; Stefanadis, Christodoulos
Abstract: Aim: We conducted a systematic review and meta‐analysis of randomized and observational studies with a control group to evaluate the effectiveness and safety of a time to isolation (TTI)‐based strategy of cryoballoon ablation (CBA) in the treatment of atrial fibrillation (AF). Methods: Three electronic databases (MEDLINE, Cochrane Central Register of Controlled Trials, and Embase) without language restrictions were searched. The intervention assessed was a TTI‐based strategy of CBA in the treatment of AF. TTI was defined as the time from the start of freezing to the last recorded pulmonary veins' potential. The comparison of interest was intended conventional protocol of CBA. The primary endpoint was freedom from atrial arrhythmia. Results: Nine studies were deemed eligible ( N  = 2289 patients). Eight studies reported freedom from atrial arrhythmia and pooled results showed a marginally similar success rate between the two protocols (odds ratio [OR]: 1.24; 95% confidence interval [CI]: 0.98–1.56). A prespecified subgroup analysis verified that a high dose TTI strategy (with >120 s duration of cryotherapy post‐TTI) compared to the conventional protocol could significantly increase the patients without atrial arrhythmia during follow‐up (OR: 1.39; 95% CI: 1.05–1.83). TTI strategy could also significantly decrease total procedure time (SMD: −26.24 min; 95% CI: −36.90 to −15.57) and phrenic nerve palsy incidence (OR: 0.49; 95% CI: 0.29–0.84). Conclusion: Moderate confidence evidence suggests that an individualized CBA dosing strategy based on TTI and extended (>2 min post‐TTI) duration of CBA is accompanied by fewer recurrences post‐AF ablation.